2022
DOI: 10.3390/plants12010111
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiles, Genetic Diversity, and Genome Size of Bulgarian Population of Alkanna tinctoria

Abstract: Alkanna tinctoria (L.) Tausch Boraginaceae is a medicinal plant whose root is used for its antimicrobial and anti-inflammatory properties. A. tinctoria roots have been subject to numerous studies. However, the aerial parts have been explored less. The objective of the present study was to compare the chemical profile of aerial parts and roots as well as the total alkannin content in roots of 11 populations of the species from different floristic regions of Bulgaria. Methanolic extracts from 22 samples were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The identified metabolites in the aerial parts of both A. orientalis and A. tinctoria have been compared with existing data from the literature [ 3 , 4 , 5 , 31 ] ( Table 4 ). It has been observed that one organic acid, eight phenolic compounds and six flavonoids are reported for the first time in the aerial parts of these species in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified metabolites in the aerial parts of both A. orientalis and A. tinctoria have been compared with existing data from the literature [ 3 , 4 , 5 , 31 ] ( Table 4 ). It has been observed that one organic acid, eight phenolic compounds and six flavonoids are reported for the first time in the aerial parts of these species in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that one organic acid, eight phenolic compounds and six flavonoids are reported for the first time in the aerial parts of these species in the current study. It is noteworthy that although caffeic acid has been referred to once in the genus [ 31 ] previously, the caffeic acid derivatives (rosmarinic acid, lithospermic acid, salvianolic acids and rabdosiin and its salts) are completely missing in the studied species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, researchers have also reported the presence of other bioactive components such as alkannins, arnebifuranone, alkandiol, napthoquinones, alkanfuranol and shikonin in A. tinctoria L. root extract [23,24,64].…”
Section: Identification Of Phytochemicals Using Gas Chromatography-ma...mentioning
confidence: 99%
“…In Ayurveda, the traditional Indian medicine, Ratanjot root is used to treat various ailments, including skin disease, digestive disorders, urinary calculi, menstruation abnormalities, and respiratory illness [14,22]. The Ratanjot root contains bioactive components known for their antiinflammatory, antimicrobial, and wound-healing properties [23][24][25]. Moreover, Ratanjot root or alkanet extracts have shown anticancer activities [25,26] and are also used in histological staining of tissue samples [16,19].…”
Section: Introductionmentioning
confidence: 99%